The Concept of Istihsan and Its Application in Sharia Economic Fatwas - Indira Rahma Annisa; I Isman; Imron Rosyadi (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyze the concept of istihsan in usul al-fiqh and examine its relevance and application in sharia economic fatwas as a response to the complexity of modern economic transactions that cannot always be resolved through general rules or qiyas jali. The research methodology used is a qualitative approach with a library research type and is normative in nature, with primary data in the form of fatwas from the National Sharia Council-Indonesian Ulema Council (DSN-MUI) relating to contemporary contracts and transactions, such as salam contracts, istisna', mu'āṭāh sales, sharia electronic money, and sharia fintech services, as well as secondary data in the form of ushul fikih and fikih muamalah literature. The analysis was conducted through content analysis and comparative-argumentative analysis to assess the shift in legal rulings from qiyas jali to the istihsan approach. The results of the study show that istihsan is used explicitly in sharia economic fatwas through various forms, such as istihsan bi al-nash, istihsan bi al-maslahah, and istihsan bi al-'urf, in order to realize benefits, justice, and convenience without violating the basic principles of sharia, particularly the prohibition of usury, gharar, and injustice. This study confirms that istihsan is a valid and relevant method of ijtihad in the development of Islamic economic fatwas, and has original value in demonstrating the adaptability of Islamic law to contemporary economic dynamics while remaining oriented towards the maqashid of Sharia.